TGFβ activity released from platelet-rich fibrin adsorbs to titanium surface and collagen membranes - Di Summa, Francesca (Sci Rep, 2020)
Platelet-rich fibrin (PRF) contains a broad spectrum of bioactive molecules that can trigger several cellular responses. However, these molecules along with their upstream responses remain mostly uninvestigated. By means of proteomics we revealed that PRF lysates contain more than 650 proteins, being TGF-β one of the few growth factors found. To uncover the major target genes regulated by PRF lysates, gingival fibroblasts were exposed to lysates obtained from PRF membranes followed by a whole genome array. We identified 51 genes strongly regulated by PRF including IL11, NOX4 and PRG4 which are characteristic TGF-β target genes. RT-PCR and immunoassay analysis confirmed the TGF-β receptor I kinase-dependent increased expression of IL11, NOX4 and PRG4. The PRF-derived TGF-β activity was verified by the translocation of Smad2/3 into the nucleus along with the increased phosphorylation of Smad3. Considering that PRF is clinically used in combination with dental implants and collagen membranes, we showed here that PRF-derived TGF-β activity adsorbs to titanium implants and collagen membranes indicated by the changes in gene expression and immunoassay analysis. Our study points towards TGF-β as major target of PRF and suggest that TGF-β activity released by PRF adsorbs to titanium surface and collagen membranes